Introduction to Coding through Digital Storytelling to Enhance The Creativity of Early Childhood - Sulistyaati, Warni; Asmawulan, Tri (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Purpose: This study aims to understand how the process of learning coding through digital storytelling takes place in early childhood education settings, as well as how children's experiences in participating in these activities emerge as a form of creativity.Methodology: This study used a descriptive qualitative method with a focus on children's experiences, perceptions, and interactions during the activities. The study was conducted at Aisyiyah Kemlayan Kindergarten, involving children aged 5-6 years old in group B. Data were collected through observation, group interviews with teachers, children, and parents, documentation of children's digital works, and focus group discussions (FGD).Results: Research shows that digital storytelling helps children explore, organize ideas, convey concepts, and tell stories more freely. Children are very interested in digital media, and they begin to show changes in creative behavior, such as the emergence of unique ideas, the courage to try new methods, and improved storytelling skills. The process of learning coding through visual and narrative elements in digital storytelling provides children with the opportunity to build story logic, enrich their imagination, and enhance their creative thinking skills.Application/Originality/Value: This study provides an understanding that digital storytelling can be a meaningful and enjoyable approach to introducing coding while facilitating creativity in early childhood in the context of technology-based learning.